Edge AI : convergence of edge computing and artificial intelligence /: convergence of edge computing and artificial intelligence. ([2020]) - Wang, Xiaofei; Han, Yiwen; Leung, Victor C. M; Niyato, Dusit; Yan, Xueqiang; Chen, Xu
No abstract available